Peningkatan Kinerja Keuangan UMKM Melalui Pendampingan Penggunaan Accurate Online - Wicaksono, Achmad; Sofa, Devi Maya; Iswanto, Denny; Hilmawan, Tanta; Andriani, Rena (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This community service aimed to improve the financial performance of MSMEs, particularly Warkop Teras Sepande Candi in Sidoarjo, through training in financial reporting using the Accurate Online application. Using the Asset-Based Community Development (ABCD) approach, the program focused on applying technology to enhance business efficiency. The use of Accurate Online significantly reduced the time needed for preparing financial reports, allowing business owners to focus more on growth strategies. It also improved report accuracy by minimizing manual errors and increased transparency to meet regulatory standards, strengthening trust with banks and auditors. The training helped MSMEs understand and utilize the application, fostering a more tech-savvy and adaptive work culture. The results not only benefited Warkop Teras Sepande but also provided a practical model for other MSMEs in managing financial records with technology. This initiative is expected to inspire broader adoption of digital tools to boost MSME competitiveness and business sustainability.